THE EVOLVING FIELD OF PUBLIC HEALTH, THE GLOBAL DISEASE PATTERNS AND THE NEED FOR CAPACITY BUILDING OF PHYSICIANS FOR HEALTH IN PAKISTAN - Abdullah, Muhammad Ahmed; Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2024)
Amongst all its South Asian and Eastern Mediterranean neighbors, Pakistan is still struggling with major public health hurdles, from elevated rates of stillbirths, infant, neonatal and under-five mortality, and maternal mortality compounded with low contraceptive prevalence rates, a surge in infectious diseases, and a notable burden of non-communicable diseases. The question arises: Are we nurturing a sufficiently skilled public health workforce? Complicating matters is a fragmented, unregulated healthcare system marked by non-uniform healthcare delivery and an acute dearth of proficient human resources. WHO's health system strengthening framework considers the health workforce as one of six critical building blocks, essential for effective public health interventions. Yet, the existing undergraduate MBBS curriculum in Pakistan tends to conflate "community medicine" with "public health," despite the latter's much bigger canvas, applications and centrality in global health in today's world. The subject of community medicine in medical colleges is still imparting rudimentary health concepts, definitions and an obsolete curriculum. To tackle evolving global health challenges, diseases patterns and cross border nature of infections, it's imperative to re-visit the MBBS curriculum. This would entail integrating scientific domains such as epidemiology, health economics, medical statistics, sociology, psychology, and health management sciences. Emphasis should be placed on cultivating research skills, promoting evidence generation, and fostering the use of information for informed decision-making. Furthermore, innovative methods for student assessment, program evaluation, and practical experiences are indispensable. Collaboration among public health practitioners, academics, and medical educators is indispensable for crafting a comprehensive and technically robust curriculum. Pakistan urgently needs an updated MBBS curriculum to confront the public health exigencies of the present era. Such a curriculum must embrace interdisciplinary subjects and inventive assessment techniques, ensuring that medical graduates are equipped to address contemporary public health emergencies.